Exploring the relationship between nutrition knowledge and mental well-being: Research on master athletes participating in recreational marathons - PEKEL, AYDIN (My University, 2023)
The present descriptive correlational study attempted to unlock the relationship between nutrition knowledge and mental well-being among master athletes participating in the 44th Istanbul Marathon. Using the convenience sampling technique, we recruited 137 master athletes, 19 females (13.9%) and 118 males (86.1%), competing in the said marathon. Besides, we collected the data using a demographic information form, the Nutrition Knowledge Level Scale for Adults (basic nutrition and nutrition-health knowledge and dietary preferences preference), and the Warwick-Edinburgh Mental Well-being Scale. Then, we utilized descriptive statistics, Pearson’s correlation analysis, and stepwise regression analysis to analyze the data. All analyses were performed on the SPSS 24.0 program, and a p-value of < 0.05 was considered statistically significant. The regression analysis revealed that the participants’ nutrition knowledge and dietary preferences significantly predicted their mental wellbeing. The relationships between nutrition knowledge, dietary preferences, and mental well-being seem to be intricate and multifaceted. Yet, previous evidence supports the idea that proper nutrition and mental well-being are positively correlated in athletics. Similarly, our findings indicated that sustaining a healthy diet and dietary preferences can contribute to athletes’ mental well-being, particularly in events demanding endurance (e.g., marathons). A well-balanced, nutrient-rich, and hydrating diet not only aids in training and recovery but also improves mental well-being. Therefore, athletes should implement a periodized, individualized plan prioritizing a variety of foods to satisfy their caloric needs.
Keywords: Nutrition; mental-well-being; recreation; master athletes